Improving the efficiency of micronozzle by heated sidewalls - Hameed, Amar Hasan; Kafafy, Raed; Asrar, Waqar; Idres, Moumen (2011)
Heat developing by electrical field within a uniform side wall of micronozzle is established and its effect on nozzle flow parameters is tested. The continuum two-dimensional flow analysis of gas and one dimensional thermal analysis of the uniform sidewall are solved numerically and simultaneously for different configurations of heat supplying. Heat developing in the convergent-divergent sidewall shows improvement of thrust level and specific impulse due to an increase in both density and pressure at the exit section, although there is a degradation of Mach number and velocity and increase in the thickness of the subsonic boundary layer. Heat generation rate can be increased under limitations of the base metal structural properties .It is observed that heat exchange at convergent and divergent sections is more effective than preheating at the straight section before the entrance of the nozzle. It is found that; choosing the inlet boundary condition at the starting point of convergence shows additional pressure losses due to hard turning of streamlines of the uniform velocity exits from a the gas chamber. Hence, shifting the inlet boundary condition upstream the nozzle is necessary to get fully developed flow entering the nozzle with smoother turning of streamlines, and to reduce pressure losses.